Essays in economics - Pigou, A. C. (London, 1952)
The economic papers collected in this volume are all, except number 18, general, not specialist in character. I have excluded purely technical discussions intended for economists, as also a number of papers that have become obsolete with the ending of the war. Those that are left, except numbers 9, 14 and 15, which were written quite recently, have all been published already - none earlier than 1939 in the places named in footnotes; and I have to thank the various persons concerned for permission to reprint them. In the fifth, I have cut out a little friendly chaff at the expense of Lord Beveridge; well enough, maybe, at the time but certainly not worth the solemnity of republication. In the seventh-a partly frivolous paper to break the aridity of the journey I have reduced the acid content a little! In the eighth I have added a note, made some small explanatory adjustments and corrected a mistake. In the tenth I have cut out an introductory paragraph and in the seventeenth added a note. In the seventeenth I have made some fairly substantial modifications. There are bound to be some repetitions-let us hope no contra dictions. It would have been wearisome to search for and excise them, and, except in one case, I have not attempted that sort of gardening. The dates of the several articles and the date of the devaluation of the £ (September 1949) should be borne in mind.
Keywords: Economics